Exploration of Herpetofauna Diversity in Banten Forest Park as a Basis for Biodiversity Information - Haryandi, Yopi; Nugraheni, Latif Sofiana (MAXIMUS: Journal of Biological and Life Sciences, 2025)
The Banten Forest Park is the only conservation area in Banten managed by the local government and possesses significant potential for high herpetofaunal diversity. This study aimed to document the diversity and composition of herpetofaunal species within the park. Data were collected using the Visual Encounter Survey (VES) method combined with exploratory techniques, conducted from June 22 to 23, 2024. A total of 43 individuals representing nine species, seven genera, six families, and three orders (Squamata, Serpentes, and Anura) were recorded. The Squamata order was the most dominant, comprising the families Agamidae, Gekkonidae, Scincidae, and Varanidae, with Sphenomorphus sanctus and Eutropis multifasciata identified as the most abundant species. All recorded species are categorized as Least Concern by the IUCN and are not listed as protected under Indonesian wildlife regulations. The Shannon–Wiener diversity index (H’ = 1.75) indicates a moderate level of species diversity. The findings collectively demonstrate that the habitat within Banten Forest Park maintains adequate ecological integrity to support a diverse community of reptiles and amphibians, underscoring the importance of conserving habitat heterogeneity in tropical lowland ecosystems.